Integral and differential developments of carrier density of states in the intercalated layered crystal - Tovstyuk, N.K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The effect of the layered crystal intercalation on the functional dependence of the carrier densityof states is analyzed. The conditions of thermodynamic stability of intercalation process dependingon Fermi energy and microscopic parameters are studied.